Private Higher Education Globally: A Distant Second Place? - Levy, Daniel (International Higher Education, 2020)
Although remaining a decided second to the public sector globally and in most countries, private higher education has been rapidly expanding and now holds a third of the world’s enrollment—and continues to grow and diversify. It has achieved significance in a variety of qualitative respects and even leadership or coleadership in some. The private sector is a prominent second sector.